Implementation of Health Education to Improve Adolescent Girls' Knowledge of the Importance of Iron Supplement Tablet Consumption at SMP Negeri 2 Gorontalo City - Sitti Rahmadiva Resita; Ani Retni; Inne Ariane Gobel (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Adolescent girls are a vulnerable group for anemia, particularly iron deficiency anemia, due to menstrual blood loss, an unbalanced diet, and low compliance with iron supplementation. Anemia in adolescent girls can lead to decreased concentration, fatigue, and long-term health problems. This study aimed to determine the effect of health education on increasing adolescent girls' knowledge about the importance of iron supplementation at SMP Negeri 2 Gorontalo City. This study used the following method: almost experimental with design pretest–posttest. The research population was all female adolescents at SMP Negeri 2, Gorontalo City, with a sample of 74 respondents selected using the technique purposive sampling. Data analysis was carried out using the paired t-test. The results of the study showed that before the health education, most respondents had a low level of knowledge (45.9%), whereas after the health education, the majority of respondents had a good level of knowledge (62.2%). The test results paired t-test showed a p-value of 0.000 (p < 0.05). This study concluded that health education significantly impacted the knowledge of adolescent girls. Schools and health workers are advised to continuously improve health education programs to prevent anemia in adolescent girls.